Shifting Rhetorical Norms and Electronic Eloquence: TED Talks as Formal Presentations. (July 2016) - Kedrowicz, April A.; Taylor, Julie L.
Advances in digital media have made an impact on traditional rhetorical culture, thus shifting expectations and norms associated with orality and public presentation. Technology, entertainment, and design (TED) talks represent a new genre of presentation characteristic of Jamieson's notion of electronic eloquence in that presenters weave together an engaging narrative complete with a strong visual presence. This study applies Bandura's social cognitive learning theory to explore how students make sense of TED talks. Students responded to two questionnaires in two different classes: a basic public speaking course and a technical communication course. The results suggest that students learn vicariously through viewing mediated presentations, thus shaping their view of public speaking as a coproduced, networked, and engaging narrative. The authors offer recommendations for communication practitioners related to electronic eloquence and the rhetorical tradition.